Surgical Treatment of Bilateral Lung Cancers: Long-Term Outcomes and Prognostic Factors - Petrella, Francesco; Frassoni, Samuele; Bagnardi, Vincenzo; Casiraghi, Monica; Brambilla, Daniela; Diotti, Cristina; Spaggiari, Lorenzo (The Thoracic and Cardiovascular Surgeon, 2019)
Background Bilateral lung neoplasms are becoming more common, but distinguishing two primary lung cancers from metastatic disease can be difficult and only long-term follow-up after treatment can disclose the real behavior of the disease.The present study aimed to identify the appropriate candidates for bilateral surgical resections from the perspective of short-term postoperative complications and long-term outcomes.Methods Two hundred and fifteen consecutive patients undergoing bilateral pulmonary resection for lung cancers over a 20-year period were analyzed. Preoperative patient characteristics were noted, including demographic information, operative details, pathologic information including histology and tumor stage according to the eighth edition of the tumor nodes metastases staging system, and the use of neoadjuvant or adjuvant treatments.Results Patients receiving the second pulmonary resection more than 24 months from the first procedure as well as patients receiving bilateral lobectomies had higher overall 3-, 5-, and 10-year survival rates compared with the others.Conclusion Patients receiving the second resection more than 24 months from the first procedure have the best long-term results irrespective of the type of resection.
Keywords: bilateral lung cancers; lobectomy; overall survival